Floating in the deep end : how caregivers can see beyond Alzheimer's - Davis, Patti (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2021)
"With the searching, exquisite prose of a loving daughter, Patti Davis provides a life raft for the caregivers of Alzheimer's patients. "For the decade of my father's illness, I felt as if I was floating in the deep end, tossed by waves, carried by currents, but not drowning. "In a singular account of battling Alzheimer's, Patti Davis eloquently weaves personal anecdotes with practical advice tailored specifically for the overlooked caregiver. After losing her father, Ronald Reagan, Davis founded a support group for family members and friends of Alzheimer's patients; drawing on those years, Davis reveals the surprising struggles and gifts of this cruel disease. From the challenges of navigating disorientation to the moments when guilt and resentments creep in, readers are guided gently through slow-burning grief. Along the way, Davis shares how her own fractured family came together, and how her father revealed his true self-always kind, even when he couldn't recognize his own daughter. The result is an achingly beautiful work on the fragile human condition from a profoundly wise and empathetic writer"--